2007
DOI: 10.1097/sla.0b013e318155a762
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Colectomy for Cancer Is Not Inferior to Open Surgery Based on 5-Year Data From the COST Study Group Trial

Abstract: Laparoscopic colectomy for curable colon cancer is not inferior to open surgery based on long-term oncologic endpoints from a prospective randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
621
3
46

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,032 publications
(693 citation statements)
references
References 25 publications
23
621
3
46
Order By: Relevance
“…This has been observed in other series as well [4,6,13,14]. A meta-analysis of the large randomized trials has shown a conversion rate of 19% [16]. However, when the patients who underwent a conversion to an open surgery were excluded, the difference was not marked.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…This has been observed in other series as well [4,6,13,14]. A meta-analysis of the large randomized trials has shown a conversion rate of 19% [16]. However, when the patients who underwent a conversion to an open surgery were excluded, the difference was not marked.…”
Section: Resultssupporting
confidence: 61%
“…Despite this, the better short term recovery of the LAC group could be demonstrated by the fewer days spent in the ICU and shorter hospital stay. This has been demonstrated in most of the other series as well [5,[10][11][12][13][14]16].…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Vários trabalhos foram realizados com o objetivo de avaliar a laparoscopia no tratamento das doenças malignas colorretais 3,4,5,6,7,8,17 . O câncer colorretal representa um problema importante de saúde pública.…”
Section: Introductionunclassified
“…Recent large RCTs [5,6] as well as a systematic review and metaanalysis of the literature [7] have reported similar advantages of laparoscopic rectal resection and total mesorectal excision (TME) compared with open surgery for extraperitoneal rectal cancer. Evidence from the literature also has shown comparable outcomes in terms of oncologic clearance and long-term survival between laparoscopic and open resection for colon [1,[8][9][10] and rectal cancer [10][11][12]. The rates for conversion of laparoscopic colon resection to open surgery reported in the largest multicenter RCTs range from 17 to 25 % [2-4], whereas the conversion rates for laparoscopic rectal resection vary between 0.6 and 32.4 % [7].…”
mentioning
confidence: 99%